A EDUCAÇÃO A DISTÂNCIA E A FORMAÇÃO DO SUJEITO: Estudo realizado sobre o professor tutor nos cursos de graduação, na modalidade a distância da Umesp, sob a ótica da multirreferencialidade - Costa, Marcos Munhoz da (2008)
The distance education (EAD) is an old method of teaching that is renewed with new information and communications technologies (ICTs). The present moment is promising for the development of research in this field since the growth of this mode of education in Brazil. Brazilian Universities (public, private, community and religious) has invested in projects in distance education; realizes that the models used in lacking precision in the settings of the functions performed by various actors in the EAD. For this reason, the work tutorial is searched with the aim of unveiling the relations between the formation of the subject and the role of the teacher mentor, considering the Institutional Educational Project and the educational project of the distance courses as well as its purposes on the anthropological concept (man), the knowledge concept and political concept (political and social relations). The assumptions that claimed the poll found a mentoring as: mediator in the process of construction and development of knowledge of the subject and as one of the team responsible for the articulation of ODL in relations with the board of faculty of the Methodist University of Sao Paulo. The text then is the result of the desire to support the development of this form of education in Brazil.(AU)